Aortic valve leaflet wall shear stress characterization revisited: impact of coronary flow. Issue 5 (4th April 2017) - Cao, K.; Sucosky, P.
Abstract: Computational characterizations of aortic valve hemodynamics have typically discarded the effects of coronary flow. The objective of this study was to complement our previous fluid–structure interaction aortic valve model with a physiologic coronary circulation model to quantify the impact of coronary flow on aortic sinus hemodynamics and leaflet wall shear stress (WSS). Coronary flow suppressed vortex development in the two coronary sinuses and altered WSS magnitude and directionality on the three leaflets, with the most substantial differences occurring in the belly and tip regions.